Optimisation of design and operating parameters of reverse osmosis process for the removal of phenol from wastewater - Shamraze Khan; Mudhar A. Al-Obaidi; C. Kara-Zaïtri; I.M. Mujtaba (South African Journal of Chemical Engineering, 2023)
Reverse Osmosis (RO) is widely used for separating organic and inorganic pollutants in wastewater. In this research, the one-dimensional steady state model of a spiral wound RO for the removal of phenol from wastewater, was simulated using gPROMS software to identify optimal design and operating parameters. The design parameters included the membrane length, width and feed spacer channel and operating conditions included temperature and pressure of the RO process. The optimal design parameters were able to maximise the removal of phenol from wastewater. The simulation results showed that the removal of phenol from wastewater was significantly influenced by the combination of membrane width, operating pressure, and feed temperature. The four main parameters (permeate concentration, solute flow, solute rejection, and water flux) that govern the performance of a reverse osmosis membrane were found to be influenced by the design and operating conditions.